2023
DOI: 10.1186/s12887-023-04243-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on clinicopathological features and prognosis of IgA vasculitis nephritis and IgA nephropathy in children

Yan Lv,
Rui Fu,
Xiao-Jie Peng
et al.

Abstract: Background IgA vasculitis nephritis (IgAVN) and IgA nephropathy (IgAN) share several clinical and pathological characteristics, though distinctions also exist. Their interrelation, however, remains undefined. This study investigates the clinicopathological divergences and prognostic disparities in pediatric patients with IgAVN and IgAN. Methods Our study encompasses 809 pediatric patients with IgAVN and 236 with IgAN, all of whom underwent kidney b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…3,4 Renal fibrosis is often synonymous with the gradual deterioration of renal function and the progression to end-stage renal disease. 5 Recently, Lv et al 6 reported that IgAN patients had higher pathological scores for complete tubular atrophy, interstitial fibrosis as well as interstitial and periglomerular inflammation compared to IgAVN patients, which is consistent with our data and strongly supports our conclusions.…”
Section: Single-cell Rna Sequencing Of Pediatric Renal Tissues Reveal...supporting
confidence: 92%
“…3,4 Renal fibrosis is often synonymous with the gradual deterioration of renal function and the progression to end-stage renal disease. 5 Recently, Lv et al 6 reported that IgAN patients had higher pathological scores for complete tubular atrophy, interstitial fibrosis as well as interstitial and periglomerular inflammation compared to IgAVN patients, which is consistent with our data and strongly supports our conclusions.…”
Section: Single-cell Rna Sequencing Of Pediatric Renal Tissues Reveal...supporting
confidence: 92%
“…Gastrointestinal involvement is relatively common in IgAV, but can vary in severity, from mild nausea to gastrointestinal bleeding and intussusception that may require surgical intervention: in a recent study about 50% of IgAV cases had gastrointestinal involvement, and 48.9% of them were classified as severe [4]. In general terms, IgAV has an overall positive prognosis with complete recovery, highly dependent on the deposition of IgA at the renal level alone [5].…”
Section: Introductionmentioning
confidence: 99%